1987
DOI: 10.1128/aem.53.6.1257-1262.1987
|View full text |Cite
|
Sign up to set email alerts
|

Citrate Metabolism by Pediococcus halophilus

Abstract: Several strains of non-citrate-metabolizing Pediococcus halophilus have previously been isolated from soy sauce mash or moromi. The factors controlling the metabolism of citrate in soy pediococci were studied. All the soy pediococcal strains tested which failed to decompose citrate did not possess citrate lyase [citrate (pro-3S)-lyase; EC 4.1.3.6] activity. In P. halophilus, citrate lyase was an inducible enzyme, and the optimum pH for activity was 7.0. The metabolism of citrate in P. halophilus was different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…Citrate and malate are the acids that lactic acid bacteria most often encounter in their food environments and in the manufacture of fermented dairy products it is desirable that they are able to metabolize the two acids into especially, acetoin and diacetyl, both regarded as being favourable in enriching the flavours of cheese, butter and other products. Several strains however, have been described as non-citrate-metabolizing strains [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Citrate and malate are the acids that lactic acid bacteria most often encounter in their food environments and in the manufacture of fermented dairy products it is desirable that they are able to metabolize the two acids into especially, acetoin and diacetyl, both regarded as being favourable in enriching the flavours of cheese, butter and other products. Several strains however, have been described as non-citrate-metabolizing strains [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Citrate metabolism is inducible in the pediococci. Citrate metabolism has been studied in several strains of soy pediococci by Kanbe and Uchida [ 19 ]. It was observed that citrate-negative strains were missing the inducible citrate lyase [citrate (pro-3S)-lyase; EC 4.1.3.6], and pathways of citrate degradation in P. halophilus differed largely from those of other lactic acid bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…In dochi, Ent. faecium seems to take the place of Tetragenococcus halophilus that is found in Japanese fermented soy sauce (Kanbe and Uchida 1987). After Ent.…”
Section: Discussionmentioning
confidence: 95%
“…As secondary effect, antimicrobial properties of diacetyl were additionally contributed to the safety of the different fermented food products (Jay 1982;Langa et al 2014). Citrate metabolism was investigated in several LAB, including pediococci strains isolated from soy products and cheeses (Kanbe and Uchida 1987;McSweeney et al 2017;Quintans et al 2008). It was observed that citrate-negative strains lack a particular enzyme, inducible citrate lyase [citrate (pro-3 S)-lyase; EC 4.…”
Section: The Taxonomy Of Pediococcusmentioning
confidence: 99%